THE INFLUENCE OF COUNTRY-OF-ORIGIN SUSTAINABILITY PERCEPTION ON CONSUMER PURCHASE INTENTION FOR CHINESE ELECTRIC VEHICLES IN INDONESIA - Nadia Adeline; Alvincia Tamara; Ruth Srininta Tarigan (Petra Christian University, 2024)
This study examines whether a country's environmental reputation influences consumer decisions to purchase its electric vehicles (EVs), focusing on Indonesian consumers' perceptions of Chinese EVs. Specifically, it investigates how perceptions of China's sustainability efforts affect purchase intention through the mediating roles of perceived quality and perceived environmental benefit. A quantitative approach was employed, surveying 218 Indonesian consumers familiar with or considering Chinese EVs using a five-point Likert scale questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that positive perceptions of China's sustainability initiatives significantly enhance both perceived quality and perceived environmental benefit of Chinese EVs. However, while both factors improve with a stronger green reputation, only perceived quality directly and substantially increases purchase intention; perceived environmental benefit, though valued by consumers, does not independently drive buying decisions. This suggests that while sustainability matters to buyers, product quality remains the decisive factor in purchasing choices. Future research could explore different cultural contexts and employ mixed-methods approaches to gain deeper consumer insight.